Pellicle frame, pellicle, exposure original plate with pellicle, method for manufacturing pellicle frame, exposure method, method for manufacturing semiconductor device, and method for manufacturing liquid crystal display panel

By mechanically grinding, electrolytic degreasing and chemical grinding of the protective film frame, the problem of residual dust particles after mechanical grinding is solved, significantly reducing the number of particles on the surface, improving the quality of the protective film frame and the lithography process stability.

CN119487445APending Publication Date: 2025-02-18SHIN ETSU CHEMICAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051912.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing protective film frame still retains dust particles after mechanical grinding, resulting in problems of foreign matter detection and adverse effects during inspection and lithography.

Method used

The protective film frame is made of pure titanium or titanium alloy, combined with mechanical grinding, electrolytic degreasing and chemical grinding treatment, significantly reducing dust particles and organic matter on the surface.

Benefits of technology

Through the above-mentioned treatment method, the number of particles on the surface of the protective film frame is significantly reduced, adverse effects caused by foreign matter during inspection and lithography are prevented, and the processing ease, light weight and heat resistance of the protective film frame are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487445A_ABST
    Figure CN119487445A_ABST
Patent Text Reader

Abstract

The present invention is a pellicle frame constituting a pellicle for lithography, the pellicle frame being made of pure titanium or a titanium alloy, and the surface of the pellicle frame being subjected to mechanical polishing treatment, electrolytic degreasing treatment, and chemical polishing treatment. As a result, provided are a pellicle frame in which dust particles remaining on the surface are reduced, and a method for manufacturing the pellicle frame.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pellicle and a pellicle frame installed as a dustproof member on a photomask for photolithography, and an exposure original plate with the pellicle, and also to a method for manufacturing the pellicle frame, an exposure method, a method for manufacturing a semiconductor device, and a method for manufacturing a liquid crystal display panel. Background Art

[0002] In recent years, the design rules of large scale integrated circuits (LSI) are being pushed towards the miniaturization of sub-quarter micron, and with this, the exposure light source is being pushed towards the shorter wavelength. That is, the exposure light source has shifted from g-rays (436nm) and i-rays (365nm) based on mercury lamps to KrF excimer lasers (248nm), ArF excimer lasers (193nm), etc., and further research has been conducted on EUV exposure using extreme ultraviolet (EUV) light with a main wavelength of 13.5nm.

[0003] In the manufacture of semiconductor devices such as LSI and VLSI or in the manufacture of liquid crystal display panels, a semiconductor chip or a liquid crystal original plate is irradiated with light to produce a pattern. If dust is attached to the photomask and reticle (hereinafter collectively referred to as the "exposure original plate") used for lithography, the dust will absorb the light or bend the light, so that the transferred pattern will be deformed or have rough edges. In addition, the base will be stained black, and there will be problems such as damage to size, quality, and appearance.

[0004] These operations are usually performed in a clean room, but even so, it is difficult to keep the exposure original plate clean all the time. Therefore, a method is generally adopted in which a protective film is attached to the surface of the exposure original plate as a dustproof member before exposure. In this case, foreign matter does not directly adhere to the surface of the exposure original plate, but to the protective film. Therefore, as long as the focus is focused on the pattern of the exposure original plate during photolithography, foreign matter on the protective film has nothing to do with transfer.

[0005] The basic structure of the protective film is as follows: a protective film sheet with high transmittance relative to the light used in exposure is tensioned on the upper end surface of a protective film frame made of metal such as aluminum, and an airtight gasket is formed on the lower end surface. The airtight gasket generally uses an adhesive layer, and a protective sheet is attached to protect the adhesive layer. The protective film sheet includes nitrocellulose, cellulose acetate, fluorine-based polymers, etc. that allow the light used in exposure (g-rays (436nm), i-rays (365nm), KrF excimer lasers (248nm), ArF excimer lasers (193nm), etc. based on mercury lamps) to pass well, but in EUV exposure applications, extremely thin silicon films or carbon films have been studied as protective films.

[0006] In the past, an aluminum frame was used for the pellicle frame. An anodized film is provided on the aluminum frame for the purpose of corrosion resistance, etc. If there are protrusions on the surface of the aluminum frame on which the anodized film is to be provided, the protrusions will remain even after the anodized film is formed. In order to prevent such a situation, it is known to subject the aluminum frame to chemical polishing treatment before providing the anodized film (Patent Document 1).

[0007] On the other hand, titanium frames for EUV are being studied. Titanium frames have high strength and corrosion resistance, so there is no need to provide an anodized film for the purpose of improving strength, as with aluminum frames. Therefore, in titanium frames, mechanical polishing is generally used to remove scratches and burrs formed during processing, which is superior in cost and productivity to chemical polishing.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 6008784 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the inventors have found that even after mechanical polishing or the like is used to remove scratches or burrs and the cleaning process is repeated several times, particles such as titanium powder generated by mechanical polishing or the like still remain on the surface of the pellicle frame. These particles are identified as foreign matter during the inspection process when manufacturing the pellicle, the inspection process when installing the pellicle, and the inspection process when using the pellicle.

[0013] Even if the particles are not detected as foreign matter in the inspection step, there is a risk that the particles may fall off the pellicle frame due to vibration or EUV irradiation when the pellicle is used.

[0014] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a pellicle frame and a method for manufacturing the pellicle frame in which dust particles remaining on the surface are reduced.

[0015] Technical means of solving problems

[0016] In order to achieve the above-mentioned object, the present invention provides a protective film frame, which constitutes a protective film for photolithography, characterized in that:

[0017] The protective film frame is made of pure titanium or titanium alloy, and the surface is

[0018] Mechanical grinding treatment,

[0019] Electrolytic degreasing treatment and

[0020] Chemical grinding treatment.

[0021] The pellicle frame of the present invention is made of titanium or a titanium alloy and therefore has excellent processing ease, light weight, heat resistance, and the like.

[0022] In addition, the dust particles or organic matter (oil, dirt, adsorbed dust, etc. attached to the surface) remaining on the surface are reduced. In addition, dust particles or organic matter are collectively referred to as particles below. Therefore, in the inspection process when manufacturing the protective film, it is possible to prevent the foreign matter inspection from being stuck due to the presence of the particles. In addition, it is possible to prevent the particles from falling from the protective film frame in the exposure environment and causing adverse effects during photolithography.

[0023] At this time, the protective film frame can be set as:

[0024] In the particle evaluation by immersing the pellicle frame in pure water and irradiating ultrasonic waves for one minute, the number of particles with a spherical equivalent diameter of 1 μm to 15 μm released into the pure water was 100 μm per 1 cm of the pellicle frame. 2 The surface area is less than 1500.

[0025] In this way, the pellicle frame is formed with the number of particles on the surface extremely reduced.

[0026] Furthermore, the unevenness present on the inner side surface of the pellicle frame may be 5 μm or less.

[0027] If the surface has irregularities, it may affect the foreign matter inspection. However, if it is suppressed to a size (height or depth) of 5 μm or less, the influence on the inspection can be reduced.

[0028] In addition, the protective film frame can be configured as:

[0029] In an ion elution test in which the ions dissolved were measured by immersing the pellicle frame in pure water at 90°C for 3 hours, the concentration of ions dissolved was measured at every 50 cm 2 The surface area of ​​the dissolved concentration meter into 100 ml of pure water,

[0030] Acetate ion is below 10ppb,

[0031] Formate ion is less than 100 ppb,

[0032] Cl ions are below 10ppb,

[0033] NO2 ions are below 10ppb,

[0034] NO3 ions are below 10ppb,

[0035] SO4 ions are below 10ppb,

[0036] Oxalate ion is below 10ppb,

[0037] PO4 ions are below 10ppb,

[0038] NH4 ions are less than 100 ppb.

[0039] In this way, if the protective film frame reduces the various ions generated, the influence of these ions on the exposure environment can be particularly reduced.

[0040] In addition, the present invention provides a method for manufacturing a pellicle frame, which is a method for manufacturing a pellicle frame constituting a pellicle for photolithography, characterized in that:

[0041] Apply to the surface of the protective film frame made of pure titanium or titanium alloy

[0042] Mechanical grinding treatment,

[0043] Electrolytic degreasing treatment, and

[0044] Manufactured by chemical grinding.

[0045] According to the manufacturing method of the pellicle frame of the present invention, a pellicle frame having excellent processing ease, light weight, heat resistance, etc. and having a reduced number of particles such as dust particles or organic matter remaining on the surface can be obtained. Furthermore, the pellicle frame can be prevented from being stuck in the inspection process or having adverse effects during photolithography due to the particles.

[0046] At this time, the mechanical grinding process may be:

[0047] Includes magnetic grinding treatment only, drum grinding treatment only, or a combination of these.

[0048] This can further reduce the amount of dust particles remaining on the surface of the pellicle frame.

[0049] In addition, the magnetic grinding process may be:

[0050] The cleaning was performed using a rod-shaped magnetic medium made of stainless steel (SUS) in the cleaning water in which the pellicle frame was immersed.

[0051] By performing the grinding process in the washing water (solvent) using the magnetic medium in this manner, even if powder of titanium or the like is generated by grinding, the powder is rapidly diffused into the solvent, and the dust remaining on the surface is significantly reduced.

[0052] In addition, the chemical grinding process may be:

[0053] Includes chemical polishing or electrolytic polishing.

[0054] If so, particles attached to the surface can be effectively removed.

[0055] In addition, the present invention provides a protective film, comprising a protective film frame and a protective film sheet tensioned on the protective film frame, and used for photolithography, wherein the protective film is characterized in that:

[0056] The protective film frame is the protective film frame described above.

[0057] In addition, the present invention provides an exposure original plate with a protective film, comprising an exposure original plate, on which a protective film is installed, wherein the exposure original plate with a protective film is characterized in that:

[0058] The protective film is the protective film described above.

[0059] With the pellicle or exposure original plate with pellicle of the present invention, the number of particles adhering to the surface of the pellicle frame is extremely small, and adverse effects in the inspection process or photolithography can be prevented.

[0060] In addition, the present invention provides an exposure method, characterized in that the exposure is performed using the exposure original plate with a protective film as described above.

[0061] In addition, the present invention provides a method for manufacturing a semiconductor device, characterized by comprising a step of performing exposure using the exposure original plate with a protective film as described above.

[0062] In addition, the present invention provides a method for manufacturing a liquid crystal display panel, characterized in that it includes a step of performing exposure using the exposure original plate with a protective film as described above.

[0063] According to the exposure method of the present invention, the number of particles adhering to the surface of the pellicle frame is extremely small, and it is possible to prevent the particles from falling from the pellicle frame in the exposure environment and causing adverse effects during photolithography.

[0064] Effects of the Invention

[0065] The present invention can reduce dust particles remaining on the surface of the pellicle frame. Furthermore, by performing chemical polishing after mechanical polishing, even if particles generated by mechanical polishing adhere to the surface of the pellicle frame, they can be removed, and particles that are dangerous to fall off later can be reduced. In addition, the height or depth of the concave and convex can be suppressed to less than 5μm, and a method for manufacturing a pellicle frame with good foreign matter detection performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] [ Figure 1 ] is a schematic diagram showing an example of the protective film frame, protective film and exposure original plate with protective film of the present invention. DETAILED DESCRIPTION

[0067] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited thereto.

[0068] As described above, as an example of a pellicle frame, a titanium pellicle frame can be cited. Generally, scratches or burrs on the surface are removed by mechanical grinding, but it is known that particles will remain on the surface, and therefore there is a risk of getting stuck in the inspection process or causing adverse effects during photolithography. Therefore, the inventors have conducted diligent research and found that if the pellicle frame is made of pure titanium or a titanium alloy and the surface is subjected to mechanical grinding, electrolytic degreasing, and chemical grinding, the number of particles on the surface can be significantly reduced, and the above-mentioned problems can be prevented, thereby completing the present invention.

[0069] Figure 1 1 shows an example of the pellicle frame of the present invention, and also shows the pellicle or the exposure original plate with the pellicle of the present invention. Figure 1 The whole is an exposed original with a protective film.

[0070] First, the overall structure will be described. The pellicle frame (hereinafter, sometimes referred to as the frame) 1 of the present invention has a film-side adhesive 2 on the upper end surface and a mask-side adhesive 3 on the lower end surface. Furthermore, a pellicle sheet 4 is stretched and arranged on the pellicle frame 1 via the film-side adhesive 2, thereby constituting the pellicle 5 of the present invention.

[0071] Furthermore, pellicle 5 is attached to exposure plate (photomask or reticle) 6 via mask-side adhesive 3 of pellicle frame 1 , thereby constituting exposure plate with pellicle 7 of the present invention.

[0072] Each part is described in detail below.

[0073] The pellicle frame 1 only needs to be in a frame shape, and its shape corresponds to the shape of the photomask to which the pellicle 5 is mounted. Generally, it is in a quadrilateral (rectangular or square) frame shape.

[0074] As described above, pellicle frame 1 has a surface for mounting pellicle sheet 4 (the upper end surface in this example) and a surface facing the photomask when the photomask is mounted (the lower end surface in this example).

[0075] The material of pellicle frame 1 is pure titanium or a titanium alloy, which is excellent in terms of ease of processing, light weight, heat resistance, and improved inspection performance.

[0076] The size of pellicle frame 1 is not particularly limited, but since the height of the EUV pellicle is limited to 2.5 mm or less, the thickness of EUV pellicle frame 1 is smaller than that and is less than 2.5 mm.

[0077] Furthermore, in consideration of the thickness of pellicle sheet 4 , mask adhesive 3 , and the like, the thickness of EUV pellicle frame 1 is preferably 1.5 mm or less.

[0078] In addition, a jig hole (not shown) used for handling or peeling the pellicle 5 from the photomask is usually provided on the side of the pellicle frame 1. The size of the jig hole is 0.5 mm to 1.0 mm in width in the thickness direction of the frame 1 (or diameter in the case of a circular shape). The shape of the hole is not limited and may be circular or rectangular.

[0079] In addition, the frame 1 is provided with a vent 8 for relieving the pressure change inside and outside the protective membrane 5. The shape and number of the vent 8 are not limited. The vent may be provided with a cutout on the upper end surface or the lower end surface of the frame 1.

[0080] In the ventilation part 8, a filter 9 may be provided to prevent foreign matter from entering the pellicle 2. There is no limitation on the location where the filter 9 may be provided, and the inside of the pellicle frame 1, the inside of the ventilation part 8, or the outside of the pellicle frame 1 may be considered. Figure 1 It is arranged on the outside of the protective film frame 1.

[0081] Furthermore, in the previous titanium pellicle frame, the surface treatment was at most mechanical grinding, but the surface of the pellicle frame 1 of the present invention was not only subjected to mechanical grinding, but also subjected to electrolytic degreasing and chemical grinding (specific examples of these treatments will be described later). Therefore, a high-quality pellicle frame with significantly reduced particles on the surface is obtained.

[0082] The dust particles attached to the pellicle frame 1 can be evaluated by measuring the number of particles when the pellicle frame 1 is immersed in pure water. The number of particles with a spherical equivalent diameter of 1 μm to 15 μm released into the pure water by irradiating the pellicle frame 1 with ultrasonic waves for one minute is 100% per 1 cm of the pellicle frame 1.2 It is particularly preferred when the number of particles is 1500 or less in the surface area. If it is such a low value, the concern that dust particles attached to the protective film frame 1 will have an adverse effect on the inspection process can be particularly reduced. It is more preferred if the number of particles is 1200 or less, and more preferably 1000 or less. Of course, the fewer the number of particles, the more preferred. If it is 0, it is extremely preferred.

[0083] In addition, as an example of the conditions of ultrasonic irradiation, for example, an oscillation frequency of 38 kHz and an irradiation time of 1 minute can be cited.

[0084] In addition, as a method for measuring the number of particles, for example, it is sufficient to measure using a liquid particle counter.

[0085] In addition, various ions generated from the pellicle frame 1 can be evaluated by, for example, an ion elution test in which the concentration of ions eluted by immersing the pellicle frame 1 in pure water at 90° C. for 3 hours is measured. In the evaluation, the concentration of ions per 50 cm of the pellicle frame 1 is measured. 2 The surface area concentration of the elution into 100 ml of pure water is preferably: acetate ion is 10 ppb or less, formate ion is 100 ppb or less, Cl ion is 10 ppb or less, NO2 ion is 10 ppb or less, NO3 ion is 10 ppb or less, SO4 ion is 10 ppb or less, oxalate ion is 10 ppb or less, PO4 ion is 10 ppb or less, NH4 ion is 100 ppb or less. If it is such a low value, the impact of various ions generated from the protective film frame on the exposure environment can be particularly reduced. The lower the value of the elution concentration of the various ions, the more preferred. If it is 0 ppb, it is extremely preferred.

[0086] As a method for measuring the elution concentration of various ions, for example, ion chromatography may be used.

[0087] In addition, even if there are bumps, i.e., steps with a size (depth or height) greater than 0 μm, on the inner side surface 10 of the pellicle frame 1, it is preferred if the size is 5 μm or less. If the bumps are small to the above extent, the influence on foreign matter inspection etc. can be reduced. Of course, it is extremely preferred if there is no step (when the bumps are 0 μm).

[0088] Furthermore, a film side adhesive 2 is provided on the upper end surface of the protective film frame 1 as described above. There is no limitation on the material of the film side adhesive 2, and known materials such as silicone adhesives or acrylic adhesives can be used. In order to strongly hold the protective film sheet 4, an adhesive with strong adhesion is preferred. There is no limitation on the shape of the film side adhesive 2, and flat processing can be performed. There is no particular limitation on the thickness of the film side adhesive 2 layer, but since there is a basic limitation of 2.5 mm on the height of the protective film 5, it is preferably 0.5 mm or less.

[0089] A mask side adhesive 3 for attaching to a photomask is formed on the lower end surface of the pellicle frame 1. The material of the mask side adhesive 3 is not limited, and known materials such as silicone adhesives or acrylic adhesives can be used. The shape of the mask side adhesive 3 is not particularly limited, and it can be flattened. There is no particular limitation on the thickness of the layer of the mask side adhesive 3, but since the height of the pellicle 5 is limited to 2.5 mm, it is preferably 0.5 mm or less.

[0090] In addition, usually, a protective cover (not shown) for protecting these adhesives can be provided in a manner of covering the film side adhesive 2 and the mask side adhesive 3. There is no particular restriction on the material of the protective cover, for example, polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), polyethylene (PE), polycarbonate (PC), polyvinyl chloride (PVC), polypropylene (PP), etc. can be used. In addition, a release agent such as a silicone release agent or a fluorine release agent can be applied to the surface as a release layer as needed. By applying the release agent, the protective cover can be easily peeled off from the adhesive 2 and the adhesive 3. There is no restriction on the shape of the protective cover, as long as it is a size that can completely cover the adhesive 2 and the adhesive 3. The shape of the protective cover can be changed on the side of the film side adhesive 2 and the side of the mask side adhesive 3. A gripping portion may be provided on a portion of the protective cover so that the protective cover can be easily gripped when peeling off the protective cover.

[0091] In addition, there is no limitation on the material of the protective film 4, but it is preferably a material with high transmittance and high light resistance at the wavelength of the exposure light source. For example, an extremely thin silicon film or a carbon film is used for EUV exposure. As carbon films, for example, films such as graphene, diamond-like carbon, and carbon nanotubes can be listed. In addition, in the case where it is difficult to operate the protective film alone, a protective film supported by a frame such as silicon can be used. In the above case, the protective film 5 can be easily manufactured by connecting the area of ​​the frame to the protective film frame 1.

[0092] The protective film 5 of the present invention can not only serve as a protective member for preventing foreign matter from adhering to the exposure original plate 6 in the exposure device, but also has a function as a protective member for protecting the exposure original plate 6 when the exposure original plate 6 is stored or transported.

[0093] The method of attaching pellicle 5 to exposure original plate 6 such as a photomask to produce exposure original plate 7 with pellicle includes the method of attaching with the mask adhesive described above, the method of electrostatic adsorption, the method of mechanical fixing, and the like.

[0094] As described above, in the pellicle frame 1, pellicle 5, and exposure original plate 7 with pellicle of the present invention, the particles such as dust particles on the surface of the pellicle frame are significantly reduced compared with the conventional products, and the particles that are dangerous to fall off later can be reduced. Therefore, it can pass the inspection process of foreign matter in each stage, and it can prevent the occurrence of problems during photolithography due to particles attached to the surface.

[0095] Next, a description will be given of the flow of a method for manufacturing a pellicle frame according to the present invention that can manufacture the pellicle frame 1 described above.

[0096] First, a material of pure titanium or titanium alloy is prepared and machined into the shape of the pellicle frame.

[0097] Then, mechanical scratches or burrs on the surface generated during machining are removed by mechanical grinding (physical grinding). As a method for mechanical grinding, for example, drum grinding and magnetic grinding can be cited. Since the possibility of residual abrasive particles or media on the frame surface is small, magnetic grinding is more preferred. Alternatively, a method that only includes a combination of these can be used.

[0098] In addition, the method of the magnetic grinding treatment or the barrel grinding treatment is not particularly limited, and a known method can be used.

[0099] As an example of magnetic polishing, a pellicle frame is placed in a PP container filled with cleaning water (e.g., a mixture of surfactant and water) and a magnetic medium (e.g., a rod-shaped medium made of SUS), and a permanent magnet disposed at the bottom of the PP container is rotated by a motor. Thus, polishing can be performed by moving the magnetic medium in the PP container and causing it to collide with the pellicle frame.

[0100] In another example of drum polishing, a pellicle frame is placed in a container filled with cleaning water and a medium, and the container is rotated / revolved or vibrated, or a rotating disk disposed at the bottom center of the container is rotated like a washing machine. In this way, polishing can be performed by causing the medium to collide with the pellicle frame.

[0101] After the mechanical polishing treatment, the pellicle frame is subjected to an electrolytic degreasing treatment. The method of the electrolytic degreasing treatment is not particularly limited, and a known method can be used. For example, in an alkaline degreasing solution, the workpiece is used as a cathode or an anode and electricity is applied, and the stirring effect of the gas generated from the surface of the workpiece is utilized, thereby effectively removing oil, dirt, adsorbed dust, etc. attached to the surface.

[0102] If organic matter is attached to the surface of the frame after mechanical polishing, uneven dissolution of the base material caused by chemical polishing as described later may occur, which may become a factor of unevenness. Therefore, if the electrolytic degreasing treatment as described above is provided before the chemical polishing, the organic matter is effectively removed, and the surface smoothness after the chemical polishing can be improved.

[0103] Then, the pellicle frame is subjected to chemical polishing. There is no particular limitation on the method of chemical polishing, and a known method can be used. For example, chemical polishing using a chemical solution of an acid or alkali system having a dissolving power, or electrolytic polishing using an electrolyte solution, etc. can be cited.

[0104] When the frame is subjected to the chemical grinding treatment, especially in the case of a titanium frame, a crystal structure will precipitate on the surface to produce grain boundaries. Although it also depends on the properties of the base material of the frame, in general, the stronger the chemical grinding treatment conditions, the easier it is for the bumps and grooves produced near the grain boundaries or the step differences between crystals to become larger. The conditions for mechanical processing, mechanical grinding treatment and chemical grinding treatment of the frame shape can be appropriately adjusted to suppress the height or depth of the bumps and grooves on the grain boundaries or the step differences between crystals produced on the surface to, in particular, less than 5 μm as described above. By suppressing it to the numerical range as described above, the impact on foreign matter inspection can be further reduced, so it is preferred.

[0105] The pellicle frame 1 of the present invention can be manufactured as described above, but the pellicle frame can also be subjected to other treatments such as coloring. In such a case, by performing chemical polishing in the final step, even if particles adhere to the surface of the pellicle frame in the previous step, they can be easily removed.

[0106] In addition, a frame cleaning step may be appropriately added during or before or after mechanical processing, mechanical grinding, electrolytic degreasing, or chemical grinding to remove grinding residues or oil. The cleaning method is not particularly limited, and known methods can be used. For example, degreasing cleaning using an alkaline aqueous solution or a neutral detergent, or ultrasonic cleaning using pure water, etc., can be mentioned.

[0107] In addition, the exposure method of the present invention uses the exposure original plate with a protective film for exposure. Moreover, the manufacturing method of the semiconductor device or liquid crystal display panel of the present invention includes a process of exposing a substrate (a semiconductor wafer or a liquid crystal original plate) using the exposure original plate with a protective film. For example, in a photolithography process, which is one of the manufacturing processes of a semiconductor device or a liquid crystal display panel, in order to form a photoresist pattern corresponding to an integrated circuit, etc. on a substrate, the exposure original plate with a protective film is set on a stepper for exposure. Generally speaking, in EUV exposure, a projection optical system in which EUV light is reflected by the exposure original plate and guided to the substrate is used, and these are performed under reduced pressure or vacuum. Thus, even if it is assumed that foreign matter is attached to the protective film during the photolithography process, these foreign matter will not be imaged on the wafer coated with the photoresist, thereby preventing short circuits or disconnections of integrated circuits, etc. caused by the image of foreign matter. Therefore, by using an exposure original plate with a protective film, the yield in the photolithography process can be improved.

[0108] Example

[0109] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples of the present invention, but the present invention is not limited thereto.

[0110] (Example)

[0111] The protective film frame is made of titanium (external dimensions 150 mm × 118 mm × 1.5 mm, frame width 4.0 mm, surface area 68 cm 2 ).

[0112] The titanium pellicle frame is placed in a PP container filled with cleaning water (specifically, magnetic polishing cleaning liquid G100 manufactured by Priority Co., Ltd.) and a magnetic medium (made of SUS) and subjected to magnetic polishing. A permanent magnet driven by a motor is arranged at the bottom of the PP container, and the motor rotates the permanent magnet to move the magnetic medium, causing it to collide with the pellicle frame, thereby performing magnetic polishing.

[0113] After the magnetic polishing treatment, the frame was cleaned with pure water, and then electrolytically degreased using a 10 g / L NaOH solution at a voltage of 6 V for 5 minutes.

[0114] Then, the frame was immersed in a chemical polishing liquid (specifically, TCP-08 manufactured by Mitsubishi Gas Chemical Co., Ltd.) to perform a chemical polishing treatment.

[0115] After the chemical polishing treatment, the frame was washed with pure water, and then immersed in pure water again to perform ultrasonic cleaning for 5 minutes.

[0116] Then, the sample was immersed in pure water again and ultrasonically cleaned for 30 minutes under reduced pressure.

[0117] The frame after ultrasonic cleaning is cleaned with pure water, and then air is blown to dry it.

[0118] The frames after the above steps were subjected to the following liquid particle evaluation.

[0119] First, 3 L of pure water was placed in a glass beaker that had been ultrasonically cleaned with pure water, and 50 ml of the pure water in the glass beaker was poured into a liquid particle counter (NP500T manufactured by Nippon Denshoku Industries Co., Ltd.) to record the control value.

[0120] Then, the frame was immersed in pure water in a glass beaker, and ultrasonic irradiation was performed at an oscillation frequency of 38 kHz for one minute, and then the frame was pulled out, and 50 ml of pure water in the glass beaker was poured into a liquid particle counter (the same measuring device as described above). The difference between the above value and the control value was recorded as the number of particles caused by the frame.

[0121] In addition, the number of particles released from the frame into the water was estimated on the assumption that the particles were uniformly diffused into the water.

[0122] (Comparative Example 1)

[0123] A titanium frame of the same shape as in the example was prepared (outer dimensions 150 mm × 118 mm × 1.5 mm, frame width 4.0 mm, surface area 68 cm 2 ).

[0124] After the frame was cleaned with pure water, an electrolytic degreasing treatment was performed using a NaOH solution with a concentration of 10 g / L at a voltage of 6 V for 5 minutes.

[0125] After the electrolytic degreasing treatment, the frame was washed with pure water, and then immersed in pure water and ultrasonically cleaned for 5 minutes.

[0126] The frame after ultrasonic cleaning is cleaned with pure water, and then air is blown to dry it.

[0127] The frame after the above steps (different from the example, magnetic polishing, chemical polishing, and 30 minutes of ultrasonic cleaning under reduced pressure were not performed) was subjected to the same liquid particle evaluation as in the example, and the measurement results in Table 1 were obtained.

[0128] (Comparative Example 2)

[0129] A titanium frame of the same shape as in the example was prepared (outer dimensions 150 mm × 118 mm × 1.5 mm, frame width 4.0 mm, surface area 68 cm 2 ).

[0130] After the frame was cleaned with pure water, an electrolytic degreasing treatment was performed using a NaOH solution with a concentration of 10 g / L at a voltage of 6 V for 5 minutes.

[0131] After the electrolytic degreasing treatment, the frame was washed with pure water, and then immersed in pure water and ultrasonically cleaned for 5 minutes.

[0132] Then, the sample was immersed in pure water again and ultrasonically cleaned for 30 minutes under reduced pressure.

[0133] The frame after ultrasonic cleaning is cleaned with pure water, and then air is blown to dry it.

[0134] The frame after the above steps (different from the example, no magnetic polishing treatment and no chemical polishing treatment were performed) was subjected to the same liquid particle evaluation as in the example, and the measurement results shown in Table 1 were obtained.

[0135] [Table 1]

[0136]

[0137] <Evaluation of particle count>

[0138] Table 1 shows the number of particles at each sphere equivalent diameter and the total value of these particles. In addition, the value obtained by dividing the total value by the surface area of ​​the pellicle frame is shown as "the number of particles per 1 cm of the pellicle frame". 2The number of particles released in the pellicle frame (pure water 50 ml)" and the converted value after expanding the value by 60 times (3L / 50ml) "Protective film frame 1cm 2 The total number of particles released (based on 3L of pure water)".

[0139] Each 1 cm of the pellicle frame 2 The number of particles per surface area, i.e., the number of particles per 1 cm2 of the protective film frame in Table 1 2 The total number of particles released (converted to 3L of pure water)" was 641 in the example, 8629 in the comparative example 1, and 1928 in the comparative example 2. As can be seen from the particle evaluation, the number of particles such as dust particles attached to the surface of the frame of the example was significantly reduced.

[0140] (Comparative Example 3)

[0141] A pellicle frame was produced in the same manner as in Example except that the electrolytic degreasing treatment and the chemical polishing treatment were not performed, and the same liquid particle evaluation as in Example was performed.

[0142] Every 1cm of the protective film frame 2 The number of particles in the surface area was 10252. This was very poor compared to 641 in the example.

[0143] This is probably because since electrolytic degreasing treatment or chemical polishing treatment was not performed, a large amount of organic matter adhering to the surface and dust particles generated by magnetic polishing treatment remained, and these could not be effectively removed by pure water cleaning.

[0144] <About ion elution test>

[0145] The ion elution amount of the pellicle frame of the embodiment and comparative example 1 and comparative example 2 was evaluated. Specifically, the pellicle frame of each example was placed in a polyethylene bag, 100 ml of pure water was added and sealed, and the bag was kept at 90°C for 3 hours. The extraction water in which the eluted components from the pellicle frame were extracted in this way was analyzed using an ion chromatograph (ICS-2100 manufactured by Thermo Fisher Scientific) at a cell temperature of 35°C and a column (IonPacAS11-HC) temperature of 40°C at 1.5 ml / min.

[0146] Acetate ions, formate ions, chloride ions, nitrite ions, nitrate ions, sulfate ions, oxalate ions, phosphate ions and ammonium ions were detected from the extracted water, and the concentration of ions per 50 cm of the protective film frame was calculated. 2 The dissolution concentration of the surface area in 100 ml of pure water.

[0147] The obtained results are shown in Table 2. The quantitative limit (lower limit) of the ion chromatograph used in the evaluation varies depending on the ion species, but is 0.01 ppm to 0.001 ppm. The unit of each numerical value in Table 2 is ppb, and "0" means that the ion species was not quantified.

[0148] [Table 2]

[0149]

[0150] As shown in Table 2, Examples and Comparative Examples 1 and 2 all showed good results with low ion elution concentrations. Considering the results of the particle number evaluation, it can be seen that Examples are high-quality pellicle frames with minimal surface particles and generated ions.

[0151] <Regarding the production of protective film>

[0152] The frame of the embodiment is cleaned with a neutral eluent and pure water, and a film-side adhesive is applied to the upper end surface of the frame in a manner to a thickness of 0.1 mm all around the frame, which is obtained by adding 1 part by mass of a hardener (PT-56 manufactured by Shin-Etsu Chemical Co., Ltd.) to 100 parts by mass of a silicone adhesive (X-40-3264 manufactured by Shin-Etsu Chemical Co., Ltd.) and stirring the mixture.

[0153] In addition, on the lower end surface of the frame, an adhesive obtained by adding 0.1 parts by mass of a hardener (L-45 manufactured by Soken Chemical Co., Ltd.) to 100 parts by mass of an acrylic adhesive (SK Dyne 1499M manufactured by Soken Chemical Co., Ltd.) and stirring the mixture is applied over the entire circumference to a thickness of 0.1 mm as a mask side adhesive.

[0154] The pellicle frame was then heated at 100°C for 12 hours to cure the adhesive on the upper and lower end surfaces. Then, an extremely thin silicon film as a pellicle sheet was pressure-bonded to the film-side adhesive formed on the upper end surface of the frame to complete the pellicle.

[0155] <About the unevenness of the inner surface>

[0156] Each corner of the pellicle frame of the example was cut off, and the step or unevenness of the inner side surface (inner wall surface) of each side was observed using a laser microscope (three-dimensional (3D) measurement laser microscope LEXT OLS4000 manufactured by Olympus).

[0157] In addition, the details of the 3D measurement laser microscope OLS400 are as follows.

[0158] Laser Scanning Microscope (LSM)

[0159] Light source: 405nm semiconductor laser

[0160] Color observation department

[0161] Light source: White light-emitting diode (LED)

[0162] The following describes the observation method. First, the four corners of the frame are cut with a cutter to make four frame pieces. The frame pieces are placed on the stage of the microscope with the inner surface of the frame piece facing the objective lens side. Hereinafter, the direction from one corner to another corner is described as the "length direction", and the direction from the upper end face to the lower end face is described as the "thickness direction".

[0163] For the central part of the length direction of the four frame pieces, a 20x objective lens (MPLAPONLEXT20, measuring area 640μm×640μm) is used to confirm the presence of bumps or steps at the grain boundaries in an area of ​​1cm along the length direction with a 1x zoom. When a length of 1cm cannot be ensured, observations are made at multiple locations in a manner that the total is 1cm. When observing with a 20x objective lens, the grains on the surface can be easily observed, and a wide range can be observed. However, in the outer edge area of ​​the frame, the frame surface is mostly inclined toward the outer edge, and sometimes there are burrs or scratches, which are not suitable for observation. Therefore, it is ideal to observe the area other than the outer edge area of ​​10% in the thickness direction.

[0164] The height or depth of the step or depression can be measured by taking an image using a laser microscope. In the case of a laser microscope, the height detection capability is low at low magnification, and it is recommended to use a 50x or 100x objective lens for high magnification measurement.

[0165] Here, depending on the size of the step or bump to be observed, a 50x (MPLAPONLEXT50, measurement area 256μm×256μm) or 100x objective lens (MPLAPONLEXT100, measurement area 128μm×128μm) is used to capture the image. The step is measured based on the captured image to measure the height or depth of the step or bump. In the step measurement, in order to remove the influence of noise or waviness, a single shot filter (one shot filter) (height noise removal, surface correction) is applied. The difference between the highest and lowest points of the step or bump is measured and confirmed to be less than 5μm. In this way, even if the protective film frame in the embodiment has bumps on the inner side, its height or depth is extremely small, and the quality can be said to be good in this aspect.

[0166] In addition, when observing, the noise removal conditions or surface correction conditions of the height of the irregularities are as follows.

[0167] [High noise removal conditions]

[0168] Saw surface

[0169] High brightness: 4095 interpolation

[0170] Low light: 0 interpolation

[0171] [Surface correction conditions]

[0172] Tilt correction (automatic)

[0173] This specification includes the following aspects.

[0174] [1]: A pellicle frame, constituting a pellicle for photolithography,

[0175] The protective film frame is made of pure titanium or titanium alloy, and the surface is

[0176] Mechanical grinding treatment,

[0177] Electrolytic degreasing treatment and

[0178] Chemical grinding treatment.

[0179] [2]: The protective film frame according to [1], wherein the protective film frame

[0180] In the particle evaluation by immersing the pellicle frame in pure water and irradiating ultrasonic waves for one minute, the number of particles with a spherical equivalent diameter of 1 μm to 15 μm released into the pure water was 100 μm per 1 cm of the pellicle frame. 2 The surface area is less than 1500.

[0181] [3]: The pellicle frame according to [1] or [2], wherein the irregularities on the inner surface of the pellicle frame are 5 μm or less.

[0182] [4]: A protective film frame according to any one of [1] to [3], wherein the protective film frame

[0183] In an ion elution test in which the ions dissolved were measured by immersing the pellicle frame in pure water at 90°C for 3 hours, the concentration of ions dissolved was measured at every 50 cm 2 The surface area of ​​the dissolved concentration meter into 100 ml of pure water,

[0184] Acetate ion is below 10ppb,

[0185] Formate ion is less than 100 ppb,

[0186] Cl ions are below 10ppb,

[0187] NO2 ions are below 10ppb,

[0188] NO3 ions are below 10ppb,

[0189] SO4 ions are below 10ppb,

[0190] Oxalate ion is below 10ppb,

[0191] PO4 ions are below 10ppb,

[0192] NH4 ions are less than 100 ppb.

[0193] [5]: A method for manufacturing a pellicle frame, which is a method for manufacturing a pellicle frame constituting a pellicle for photolithography, wherein:

[0194] Apply to the surface of the protective film frame made of pure titanium or titanium alloy

[0195] Mechanical grinding treatment,

[0196] Electrolytic degreasing treatment, and

[0197] Manufactured by chemical grinding.

[0198] [6]: The method for manufacturing a protective film frame according to [5], wherein the mechanical grinding process only includes

[0199] Magnetic grinding treatment, drum grinding treatment or a combination of these.

[0200] [7]: The method for manufacturing a protective film frame according to [6], wherein the magnetic grinding process is

[0201] This was performed using a rod-shaped SUS magnetic medium in the washing water in which the pellicle frame was immersed.

[0202] [8]: The method for manufacturing a pellicle frame according to any one of [5] to [7], wherein the chemical polishing treatment comprises

[0203] Chemical grinding or electrolytic grinding.

[0204] [9]: A protective film, comprising a protective film frame and a protective film sheet tensioned on the protective film frame, and used for photolithography, wherein:

[0205] The protective film frame is a protective film frame according to any one of [1] to [4].

[0206]

[10] : An exposure original plate with a protective film, comprising an exposure original plate, on which a protective film is installed, wherein:

[0207] The protective film is the protective film according to [9].

[0208]

[11] : An exposure method, comprising performing exposure using the exposure original plate with a protective film according to

[10] .

[0209]

[12] : A method for manufacturing a semiconductor device, comprising the step of performing exposure using the exposure original plate with a protective film according to

[10] .

[0210]

[13] : A method for manufacturing a liquid crystal display panel, comprising a step of exposing the exposure plate with a protective film according to

[10] .

[0211] The present invention is not limited to the above-described embodiments, which are merely examples, and any device having substantially the same structure as the technical concept described in the claims of the present invention and exhibiting the same function and effect is within the technical scope of the present invention.

Claims

1. A pellicle frame, constituting a pellicle for photolithography, characterized in that: The protective film frame is made of pure titanium or titanium alloy, and the surface is Mechanical grinding treatment, Electrolytic degreasing treatment and Chemical grinding treatment.

2. The protective film frame according to claim 1, characterized in that: The protective film frame In the particle evaluation by immersing the pellicle frame in pure water and irradiating ultrasonic waves for one minute, the number of particles with a spherical equivalent diameter of 1 μm to 15 μm released into the pure water was 100 μm per 1 cm of the pellicle frame. 2 The surface area is less than 1500.

3. The protective film frame according to claim 1, characterized in that: The unevenness present on the inner side surface of the pellicle frame is 5 μm or less.

4. The protective film frame according to claim 1, characterized in that: The protective film frame In an ion elution test in which the ions dissolved were measured by immersing the pellicle frame in pure water at 90°C for 3 hours, the concentration of ions dissolved was measured at every 50 cm 2 The surface area of ​​the dissolved concentration meter into 100 ml of pure water, Acetate ion is below 10ppb, Formate ion is less than 100 ppb, Cl ions are below 10ppb, NO2 ions are below 10ppb, NO3 ions are below 10ppb, SO4 ions are below 10ppb, Oxalate ion is below 10ppb, PO4 ions are below 10ppb, NH4 ions are less than 100 ppb.

5. A method for manufacturing a pellicle frame, which is a method for manufacturing a pellicle frame constituting a pellicle for photolithography, characterized in that: Apply to the surface of the protective film frame made of pure titanium or titanium alloy Mechanical grinding treatment, Electrolytic degreasing treatment, and Manufactured by chemical grinding.

6. The method for manufacturing a protective film frame according to claim 5, characterized in that: The mechanical grinding process only comprises Magnetic grinding treatment, drum grinding treatment or a combination of these.

7. The method for manufacturing a protective film frame according to claim 6, characterized in that: The magnetic grinding process is This was performed using a rod-shaped stainless steel magnetic medium in the cleaning water in which the pellicle frame was immersed.

8. The method for manufacturing a protective film frame according to any one of claims 5 to 7, characterized in that: The chemical grinding process comprises Chemical grinding or electrolytic grinding.

9. A protective membrane, comprising a protective membrane frame and a protective membrane sheet tensioned on the protective membrane frame, and used for photolithography, wherein the protective membrane is characterized in that: The protective film frame is the protective film frame according to any one of claims 1 to 4.

10. An exposure original plate with a protective film, comprising an exposure original plate, on which a protective film is installed, characterized in that: The protective film is the protective film according to claim 9.

11. An exposure method, characterized in that: The exposure is performed using the exposure original plate with a pellicle as claimed in claim 10.

12. A method for manufacturing a semiconductor device, characterized in that: The method comprises the step of performing exposure using the exposure original plate with a protective film as claimed in claim 10.

13. A method for manufacturing a liquid crystal display panel, characterized in that: The method comprises the step of performing exposure using the exposure original plate with a protective film as claimed in claim 10.

Citation Information

Patent Citations

  • Method of operating boiling water reactor

    JP1985008784A